Incidence of positive blood aspiration following inferior alveolar nerve block - Dr Nipon Chaisrisookumporn (Elsevier, 2023)
Aim or Purpose: To compare the incidence of positive blood aspiration into the dental anesthetic cartridge between the non-aspirating dental syringe and the aspirating dental syringe following inferior alveolar nerve block. Materials and Methods: [DESIGN: Randomized Controlled Trial. (Trial Registration: TCTR 20190727001)]. One thousand and twenty-six patients, who need inferior alveolar nerve block before dental surgical procedure, were randomly included in the study. Block randomization was used to select either non-aspirating dental syringe or aspirating dental syringe (right side or left side). All patients were anesthetized with the same type of dental needle, the same type of local anesthetic agent by the same surgeon. Observation of positive or negative blood aspiration into the dental anesthetic cartridge. Comparing of the systolic blood pressure, diastolic blood pressure and pulse rate both pre-injection and immediately post-injection using the same digital blood pressure monitor. Results: Positive blood aspiration in the non-aspirating dental syringe group (11.3 %) was statistically significant less than positive blood aspiration in the aspirating dental syringe group (19.1 %) (p=0.001). There was no statistically significant difference between the pre-injection and immediately post-injection systolic blood pressure and pulse rate. Although the pre-injection and immediately post-injection diastolic blood pressure was statistically significant difference, it was not clinically difference. Conclusions: The non-aspirating dental syringe can be used to give local anesthetic agent with inferior alveolar never block.